KOMBINASI PROBIOTIK CAIR DAN TEPUNG PISANG (Musa sp.) SEBAGAI SUPLEMEN PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN NILA (Oreochromis Niloticus) - Ahmad, Fadel Ogi Putra; Grandiosa, Roffi; Maulina, Ine; Herawati, Titin (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
This studi aims to determine the optimum level of addition of liquid probiotics and banana flour in feed on the growth rate and survival of tilapia seeds. The method used in this research. Was a Completely Randomized Design (CRD) experimental method, which consisted of six treatments and three replications. The treatments were (Feed A) without the addition of liquid probiotics and banana flour; (Feed B) Addition of 15 ml/kg; (Feed C) Addition of liquid probiotics 15 ml/kg and 5 g/kg of banana flour; (Feed D) Addition of liquidprobiotics 15 ml/kg and 7.5 g/kg of banana flour; (Feed E) Addition of liquid probiotics 15 ml/kg and 10 g/kg of banana flour; and (Feed F) Addition of liquid probiotics 15 ml/kg and 12.5 g/kg of banana flour. The research fish used were 270 tilapia seeds with a size of 6-8 cm and a weight of 4-6 g. The container used is aquarium with a size 35 x 40 x 20 cm3 as many as 18 aquariums with a density of 15 tilapia feeds per treatment. Parameters observed for 40 days were absolute length growth, absolute weight growth, daily growth rate, feed conversion ratio, survival rate, and water quality including temperature, pH, and dissolved oxygen. The research results showed that the addition of 15 ml/kg liquid probiotics and 12.5 g/kg banana flour to the feed gave the best results by giving an absolute length growth of 3.14 cm, a weight growth of 9,80 g, a daily growth rate of 24.50%, the food conversion ratio is 1.36, the survival rate is 95.56%, and the water quality produced is in accordance with water quality standards covering temperature ranging from 24,9 to 27.4C, the pH of the water ranges from 6.5 to 7.4, and dissolved oxygen ranges from 5 to 6.7 mg/L.